2010
DOI: 10.1111/j.1574-695x.2010.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Participation of theCandida albicanssurface antigen in adhesion, the first phase of biofilm development

Abstract: The lack of work dealing with possible ways of reducing biofilm production via inhibiting Candida albicans adherence in the first stage of biofilm formation was a motivation for this study. The study was focused on two questions: (1) can a decrease in adherence affect the quantity of mature biofilm? and (2) can blocking the surface C. albicans complement receptor 3-related protein (CR3-RP) with polyclonal anti-C3-RP antibody or monoclonal antibody OKM1 significantly contribute to a reduction in adherence durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
3
12
0
Order By: Relevance
“…Taking into consideration the results summarizing the degree of attached cells and kinetic pattern of adherence to polystyrene, the first 30 min of interaction seems to be equally critical for the cell attachment of tested strains of both spp. The observation that the first 30 min are critical for adhesion confirmed results previously described by Bujdakova et al [32] in biofilm model with the C. albicans standard strain SC 5314 and other clinical isolate than tested in this study.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Taking into consideration the results summarizing the degree of attached cells and kinetic pattern of adherence to polystyrene, the first 30 min of interaction seems to be equally critical for the cell attachment of tested strains of both spp. The observation that the first 30 min are critical for adhesion confirmed results previously described by Bujdakova et al [32] in biofilm model with the C. albicans standard strain SC 5314 and other clinical isolate than tested in this study.…”
Section: Discussionsupporting
confidence: 79%
“…However, the degree of colonization of any surface is not only dependent on the adhesive properties of individual strains, but the duration and kinetics of adhesion can also be important. The context of the interactions between Candida cells and their adhesion to various surfaces has recently been investigated [32][33][34][35]. The results of our study do not indicate a significant difference in adhesion to a polystyrene surface between the tested clinical and nonclinical strains, with the exception of C. dubliniensis 539.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…A polyclonal anti- C. albicans antibody produced in chicken egg yolk prevented the adherence and biofilm formation by multiple Candida species (94). Antibody blocking of the C. albicans complement receptor 3-related protein significantly reduced adhesion and subsequent biofilm formation (95). Martinez and colleagues studied the effect of combinations of conventional antifungals and specific monoclonal antibodies against C. neoformans biofilms; however, the antibodies displayed a mostly antagonistic effect in combination with the antifungal drugs (96, 97).…”
Section: Development Of Novel Strategies and Therapeutics To Combat Amentioning
confidence: 99%
“…However, their applicability in treating biofilm-related infections is still in a preliminary state. In that framework, recent data showed that pretreatment of C. albicans cells with antibodies targeting the complement receptor 3-related protein led to reduced adhesion and biofilm formation in vitro [169]. In another study, anti- C. albicans antibodies from chicken egg yolk were employed as antiadherent molecules [170].…”
Section: Antibiofilm Strategies: Research and Developmentmentioning
confidence: 99%